Improving Performance Through Transformational Leadership and Self-Efficacy: Mediating role of Innovative Work Behavior - Linda Erlina; Hujjatullah Fazlurrahman; Dwiarko Nugrohoseno; Dewie Tri Wijayati Wardoyo (Relevance: Journal of Management and Business, 2023)
This study aims to determine the relationship between transformational leadership and self-efficacy on employee performance through innovative work behavior as a mediating variable. This research is a quantitative. The number of samples used was 90 employees at chemical industry company. The data in this study were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 4.0 software. The results of this study indicate that there is an effect of the transformational leadership relationship on employee performance, self-efficacy has no effect on employee performance, transformational leadership has an effect on innovative work behavior, self-efficacy has an effect on innovative work behavior, innovative work behavior mediates the relationship between transformational leadership and employee performance, innovative work behavior mediates the relationship between self-efficacy and employee performance.